Circular mucosal and submucosal resection of low-ampullary region of the rectum (stapled hemorrhoidopexy) at treatment of chronic hemorrhoids - A. M. Kuzminov; Yu. Yu. Chubarov; A. A. Tikhonov; Sh. T. Minbayev; V. Yu. Korolik (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To highlight experience of treatment of patients after circular mucoso-submucosal resection of low-ampullary region of the rectum (stapled hemorrhoidopexy) with clinical and instrumental investigation of operated patients in early and remote postoperative periods.Material and methods. Monitoring of 197 patients with hemorrhoids, operated by specified procedure was carried out. The age of patients varied from 27 years to 71 years (average – 43,5±10,6 year). Of them 118 (59,8%) were men and 79 – (40,2%) women.Results. Considered method is an efficient treatment mode for hemorrhoids of II–IV stages. Operation is followed by long-lasting clinical effect, small number of postoperative complications and reduces terms of aftertreatment of operated patients.Conclusion. Pathogenetic validity of this operation basing on mechanical and vascular theories of hemorrhoids development is proved.